Respuesta :
By the chain rule,
[tex]h(x)=g(f(5x))\implies h'(x)=5g'(f(5x))f'(5x)[/tex]
so
[tex]h'(1)=5g'(f(5))f'(5)[/tex]
It's kinda hard to tell which values are which in the table, but if I had to guess, you should get
[tex]h'(t)=5g'(f(5))f'(5)=5g'(2)(0)=0[/tex]
[tex]h(x)=g(f(5x))\implies h'(x)=5g'(f(5x))f'(5x)[/tex]
so
[tex]h'(1)=5g'(f(5))f'(5)[/tex]
It's kinda hard to tell which values are which in the table, but if I had to guess, you should get
[tex]h'(t)=5g'(f(5))f'(5)=5g'(2)(0)=0[/tex]
Answer:
The value of h'(1) is 0.
Step-by-step explanation:
It is given that h(x) = g[f(5x)].
Using chain rule, differentiate with respect to x.
[tex]h'(x)=g'[f(5x)]\times f'(5x)\times 5[/tex]
We have to find the value of h'(1).
[tex]h'(1)=g'[f(5(1))]\times f'(5(1))\times 5[/tex]
[tex]h'(1)=g'[f(5)]\times f'(5)\times 5[/tex]
[tex]h'(1)=g'(2)\times (0)\times 5[/tex] [tex][\because f(5)=2, f'(5)=0][/tex]
Product of 0 and any real number is 0.
[tex]h'(1)=0[/tex]
Therefore the value of h'(1) is 0.